STUDENT'S THINKING PROCESS IN SOLVING PROBLEMS IN TERM OF GUARDIAN AND IDEALIST PERSONALITY TYPES - Islamiah, Nur; Lefrida, Rita; Nurhayadi, Nurhayadi; Rochaminah, Sutji (Universitas Sembilanbelas November Kolaka, 2024)
This study aims to describe the thought process of students in solving problems in terms of personality types guardian and idealist in class XI SMA Negeri 5 Palu. This research is a qualitative descriptive research. The main instrument in this research is the researcher himself and the supporting instruments are The Keirsey Temperament Sorter (KTS), math problems, and interviews. The results of this study show that guardian students and idealist students are able to perform all stages of the thinking process in solving math problems, namely receiving information, processing information, and forming conclusions. Guardian and idealist students at the stage of receiving information read the problem well. Guardian students read enough once to understand the problem, while idealist students read repeatedly to understand the problem. At the information processing stage, guardian students can explain the problem solving plan while idealist students have difficulty explaining the solution plan. At the conclusion formation stage, guardian students consistently solve the problem according to what was previously planned. idealist students at the conclusion formation stage can solve the problem even though at the information processing stage they cannot explain the solution plan.